Analysis of Antecedent and Outcome Factors of Employee Voice Behavior: A Systematic Literature Review - Ashfan, Mahadharu Ashifaati; Afrianty, Tri Wulida; Utami, Hamidah Nayati (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This research provides an integrative and comprehensive review of 158 articles on employee voice behavior over 53 years (1970–2023) using the Systematic Literature Review (SLR) research method. The aim is to provide information about the concepts, factors, and outcomes influencing Employee Voice Behavior in companies and identify research gaps for future studies. Design/Method/Approach: This research uses the Systematic Literature Review method, which involves software such as VOSViewer, Publish or Perish, and Mendeley. These tools facilitate the systematic analysis of selected articles. Findings: Research findings show a significant increase in using Employee Voice Behavior topics in research publications. In general, employee voice behavior is influenced by five main elements: individual characteristics, attitudes and perceptions towards work and the organization, feelings and beliefs, behavior of superiors and leaders, and contextual factors. These elements provide room for further investigation by future researchers. Originality/Value: This research makes a significant contribution to the literature by offering a comprehensive analysis of decades of Employee Voice Behavior research. By identifying key influencing factors and trends, this research enriches our understanding of this pivotal aspect of organizational behavior, thereby enhancing the body of knowledge in this field. Practical/Policy Implications: The insights gleaned from this research carry significant practical implications for organizations and policymakers. Understanding the factors that shape employee voice behavior can be a powerful tool in the arsenal of HR practices, leadership development, and organizational policies. These insights can be harnessed to foster employee participation and engagement, thereby enhancing organizational effectiveness.